Bookkeeping practices and SME performance: The intervening role of owners’ accounting skills - Vincent Adela; Samuel Kwaku Agyei; Siaw Frimpong; Damankah Beatrice Awisome; Ahmed Bossman; Robert Ofori Abosompim; Joseph Kofi Obeng Benchie; Abdul Mujeeb Agyemang Ahmed (Heliyon, 2024)
Aside from statutory requirements, Small and Medium-Sized Enterprises (SMEs) hardly take into consideration reliable accounting systems. Therefore, poor and ineffective bookkeeping has contributed to the collapse of some SMEs. This paper examines the intervening role of owners' accounting skills in the relationship between bookkeeping practices and the performance of SMEs in the Ho Municipal Assembly of Ghana using a sample of 296 SMEs. In a structural equation modelling (SEM) framework, the Smart Partial Least Squares (Smart-PLS) software is employed to analyse the relationships between owners' accounting skills, bookkeeping practices, and the performance of SMEs. We find that bookkeeping practices and owners' accounting skills have significant positive effects on the performance of SMEs. Most importantly, we show the existence of a significant indirect relationship between bookkeeping practices and SME performance such that owners' accounting skills positively intervenes the relationship between bookkeeping practices and SME performance. Thus, in the presence of higher owners’ accounting skills, the relationship between bookkeeping and the performance of SMEs is strengthened further. In a typical emerging economy context, while appropriate regulatory bodies, such as the National Board for Small Scale Industries (NBSSI), in the Ghanaian context, and local revenue collection authorities could put forth measures like periodic compliance audits to ensure that registered SMEs are managed by skilled personnel, fostering them to meet basic requirements for keeping records and managing their accounts to improve their performance, it is worth acknowledging that the onus lies on SME managers to recognise the relevance of good recordkeeping and account management practices to ensure sustained business performance.